The Effect of Capital Structure, Firm Size, and Corporate Governance on Firm Value with Profitability Ratio as a Moderating Variable in Islamic Banks in Indonesia and Malaysia - Sulthan Ghazwah Adammakna; Diyah Ariyani (Talaa : Journal of Islamic Finance, 2025)
Indonesia and Malaysia are two countries with relatively strong Islamic banking systems. In both countries, the capital market has experienced considerable fluctuations, particularly in the Islamic banking sector. The purpose of this study is to analyze the factors that affect firm value in the Islamic banking industry in Indonesia and Malaysia. The data used in this research are secondary data gained from the quarterly reports of each Islamic bank in Indonesia and Malaysia. The data analysis techniques employed descriptive data analysis, classical assumption testing, cluster robust standard error regression testing, and moderated regression analysis (MRA). The findings indicate that capital structure, firm size, good corporate governance and probability ratio has no significant effect on firm value. Furthermore, the profitability ratio is also able to moderate the relationship between capital structure, firm size, and good corporate governance on firm value.